Synthesis of NiFeOx nanocatalysts from metal–organic precursors for the oxygen evolution reaction. Issue 30 (13th July 2022) - Nguyen, Quyen T.; Robert, Francois; Colliere, Vincent; Lecante, Pierre; Philippot, Karine; Esvan, Jérome; Tran, Phong D.; Amiens, Catherine
Abstract : Organometallic synthesis of NiFe oxide nanoparticles provided 4 nm large nanocatalysts with activity in water splitting that depended on their NiFe ratio and surface state and was optimum for a Ni2Fe1 composition and aminophosphonic acid coating. Abstract : Production of hydrogen from a renewable source that is water requires the development of sustainable catalytic processes. This implies, among others, developing efficient catalytic materials from abundant and low-cost resources and investigating their performance, especially in the oxidation of water as this half-reaction is the bottleneck of the water splitting process. For this purpose, NiFe-based nanoparticles with sizes ca . 3–4 nm have been synthesized by an organometallic approach and characterized by complementary techniques (WAXS, TEM, STEM-HAADF, EDX, XPS, and ATR-FTIR). They display a Ni core and a mixed Ni–Fe oxide shell. Once deposited onto FTO electrodes, they have been assessed in the electrocatalytic oxygen evolution reaction under alkaline conditions. Three different Ni/Fe ratios (2/1, 1/1 and 1/9) have been studied in comparison with their monometallic counterparts. The Ni2Fe1 nanocatalyst displayed the lowest overpotential (320 mV at j = 10 mA cm −2 ) as well as excellent stability over 16 h.